Producing the digital soil fertility map of Karelia - S. G. Novikov (Бюллетень Почвенного института им. В.В. Докучаева, 2020)
Recent advancements in soil digital mapping have opened new opportunities for handling the scientific and applied problems of ecological soil monitoring, inventory of land and soil resources, and are generally helpful in optimizing the management of natural resources. For Karelia the development of forest soil assessment techniques is essential, considering that 95% of the republic’s land is forest soils. This paper tells about the process of creating an updated digital map of forest soils fertility in Karelia, scale 1 : 500 000. To this end, the archival soil productivity map of the republic, produced in paper version by R.M. Morozova in 2000, was scanned and converted into a vector layer with the use of the MapInfo Professional 8.5 software package. The resultant layer was aligned with the existing digitalized soil map of Karelia, which served as the basis for constructing the thematic layer according to the data on the fertility of each soil type. As a result of this study, the soil fertility assessment scale was specified and the percentage ratio of soils of different productivity in Karelia was calculated. The digital soil fertility map is an important information source of archival and modern data, and also is a part of the GIS for soils of Karelia.